1997
DOI: 10.1016/s0741-5214(97)70317-3
|View full text |Cite
|
Sign up to set email alerts
|

Prosthetic above-knee femoropopliteal bypass grafting: Results of a multicenter randomized prospective trial

Abstract: The fact that these two prosthetic grafts performed in equivalent fashion in a controlled, well-conducted prospective study is not surprising in spite of the previous work that suggested differences. If the preferential use of synthetic bypass grafts above the knee is to be used, it should be restricted to older nonsmokers with favorable anatomy. In that instance, the choice of graft material will depend on handling characteristics and cost. Above-knee prostheses should be only selectively used in younger, smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
0
7

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(90 citation statements)
references
References 15 publications
(1 reference statement)
5
78
0
7
Order By: Relevance
“…63,132,221,278 In their analysis of patients with aortoiliac occlusive disease treated with a combination of surgical and endovascular techniques, Ballard and colleagues 221 found a relative risk of 4.6 for bypass or stent thrombosis in women. Green et al 143 observed a gender-specific relationship between graft size and thrombosis among patients treated with prosthetic aboveknee femoropopliteal bypass; 5-year cumulative patency rates in that report were 69.1% versus 37.9% for men with large versus small grafts and 45% for women in both graft-size categories.…”
Section: Patencymentioning
confidence: 99%
“…63,132,221,278 In their analysis of patients with aortoiliac occlusive disease treated with a combination of surgical and endovascular techniques, Ballard and colleagues 221 found a relative risk of 4.6 for bypass or stent thrombosis in women. Green et al 143 observed a gender-specific relationship between graft size and thrombosis among patients treated with prosthetic aboveknee femoropopliteal bypass; 5-year cumulative patency rates in that report were 69.1% versus 37.9% for men with large versus small grafts and 45% for women in both graft-size categories.…”
Section: Patencymentioning
confidence: 99%
“…2 Several studies have explored side-by-side comparisons of Dacron and ePTFE for above-knee applications and found no statistically significant differences in patency between the 2 conduits. 4,5 However, when separated by location of distal anastomosis, the patency rate of ePTFE for infragenicular anastomoses tended to be better compared with Dacron (60% versus 46%, respectively); however, this difference was not statistically significant. 5 Hobson et al 6 also examined the difference between ePTFE and composite Dacronautogenous vein grafts to the below-knee popliteal artery.…”
Section: Prosthetic Bypass Graftingmentioning
confidence: 90%
“…Reverse greater saphenous vein bypasses and artificial bypasses have a 5-year patency of about 60 % and 40 %, respectively [6]. Abbott et al, in a large multicenter study, reported a 58 % primary patency rate and a 75 % secondary patency rate for above-knee femoropopliteal bypass at 3 years [7].…”
Section: Discussionmentioning
confidence: 99%